2015
DOI: 10.1007/s10265-015-0720-0
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal translocation identified in Vigna angularis dominates the wild population in East Japan

Abstract: Using an F2 population derived from cultivated and wild azuki bean, we previously detected a reciprocal translocation and a seed size QTL near the translocation site. To test the hypothesis that the translocation in the cultivated variety contributed to the larger seed size, we performed further linkage analyses with several cross combinations between cultivated and wild azuki beans. In addition, we visually confirmed the translocation by cytogenetic approach using 25 wild and cultivated accessions. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The translocation was reciprocal-translocation where LG4 and LG6 were intermingled. This translocation was found in many accessions of wild azuki bean and it possibly affected fitness of those wild accessions to some environments and seed size [47]. In our study, comparative linkage analysis revealed macro-translocation between our zombi pea linkage map and the zombi pea linkage map developed by Marubodee et al [33]; a part of LG10 of the latter translocated to LG7 of the former (Fig 3).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The translocation was reciprocal-translocation where LG4 and LG6 were intermingled. This translocation was found in many accessions of wild azuki bean and it possibly affected fitness of those wild accessions to some environments and seed size [47]. In our study, comparative linkage analysis revealed macro-translocation between our zombi pea linkage map and the zombi pea linkage map developed by Marubodee et al [33]; a part of LG10 of the latter translocated to LG7 of the former (Fig 3).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, a part of the LG7 appeared to be duplication of LG2 or vice versa (Fig 3). Intraspecific macro-translocation has been demonstrated in azuki bean by means of comparative linkage mapping and fluorescence in situ hybridization [46,47]. The translocation was reciprocal-translocation where LG4 and LG6 were intermingled.…”
Section: Discussionmentioning
confidence: 99%
“…angularis ), we also suggested reciprocal translocation between LG4 and LG6 based on the comparison of SSR-based linkage maps developed for 2 different mapping populations [ 29 , 30 ]. Recently, this translocation event was confirmed to be occurred on a Japanese wild azuki bean parent by BAC-fluorescence in situ hybridization (FISH) analyses [ 62 ]. In that study, 21 wild azuki bean accessions collected from various regions of Japan were analyzed and it was found that geographical distribution of accessions with translocated chromosomes were restricted to eastern and northern Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The BAC library construction and screening were performed as described by Wang et al (2015). The DNA markers “38930_set1” and ”39010_set1” were used for screening (Supplemental Table 2).…”
Section: Methodsmentioning
confidence: 99%